2011
DOI: 10.1002/btpr.539
|View full text |Cite
|
Sign up to set email alerts
|

High‐density microcarrier cell cultures for influenza virus production

Abstract: Influenza virus A/PR/8/34 virus propagation in adherent Madin-Darby canine kidney cells in high-density microcarrier cultures is described. To improve virus yields, perfusion and repeated fed-batch modes were applied using cell-specific feed rates. Cell densities up to 1.1 × 10(7) cells/mL were achieved. Cell-specific virus yields in high-density cultures were at similar levels compared with standard, low-density cultivations. In the average 2,400 and 3,300 virions per cell were obtained for two variants of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 44 publications
(55 reference statements)
1
31
0
Order By: Relevance
“…The cultivation was performed under glucose and glutamine-limited conditions in fed-batch mode and, as a consequence, the cells metabolized these substrates more efficiently (Ljunggren and Häggström, 1994). For highdensity cultivation of adherent MDCK cells a repeated fedbatch operation was established, which also reduced the concentration of unwanted by-products of the cellular metabolism by removal of medium after defined time intervals (Bock et al, 2010). Irani et al (1999) presented a different approach to avoid ammonia accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…The cultivation was performed under glucose and glutamine-limited conditions in fed-batch mode and, as a consequence, the cells metabolized these substrates more efficiently (Ljunggren and Häggström, 1994). For highdensity cultivation of adherent MDCK cells a repeated fedbatch operation was established, which also reduced the concentration of unwanted by-products of the cellular metabolism by removal of medium after defined time intervals (Bock et al, 2010). Irani et al (1999) presented a different approach to avoid ammonia accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, , current strategies include both simple and straightforward processes of fresh medium addition 12 and medium exchanging, and the relatively complex processes like fedbatch and perfusion. [13][14][15][16][17][18][19] In particular, one reported approach utilizes an alternating tangential flow (ATF) system. 18 With eight successful high cell-density ATF perfusion runs for the production of H1N1 virus, it was demonstrated that cell-specific virus yields could be kept constant and cell-specific infectious virus titers were even higher than those of batch cultures (Fig.…”
Section: Current Strategies To Overcome Nutritional Limitationmentioning
confidence: 99%
“…[9][10][11] Not surprisingly, the common maintaining media used in virus production processes cannot provide sufficient nutrients in general and additional supplementation of nutrients must be performed. Currently, several strategies have been exploited to address this issue of nutritional limitation, including fresh medium replenishment, medium-exchanging, fed-batch, perfusion, etc.. [12][13][14][15][16][17][18] However, a rational design of medium supplementation based on comprehensive nutritional analyses for cells during virus production phase is still missing. Only through a detailed analysis on the differences in the cellular metabolism before and after viral infection, an insight understanding of real nutritional requirements during virus production phase can be achieved, and a rational design of medium supplementation can be solid.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, tremendous progress has been made in improving the cultivation of HPAIVs in MDCK cells using microcarrier beads in bioreactors (Bock et al 2011;Genzel et al 2004;Genzel et al 2006;Hu et al 2011;Hu et al 2008;Liu et al 2012;Tree et al 2001), and some investigations on the immunogenicity and reactogenicity of the MDCK-derived HPAIV vaccines have been reported (Doroshenko and Halperin 2009;Palache et al 1997). Nevertheless, differences among the influenza virus subtypes require modifications to the microcarrier-based MDCK cell culture conditions, including the medium formulation, agitation speed, pH, dissolved oxygen, and temperature (Bock et al 2011;Genzel et al 2004;Genzel et al 2006;Hu et al 2011;Hu et al 2008;Liu et al 2012;Tree et al 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the emergence of new viral strains responsible for global pandemics requires a switch in vaccine production from the seasonal to the pandemic vaccine. However, the pandemic vaccine manufacturing processes are currently a bottleneck and unable to meet the global vaccination demand (Bock et al 2011;Hu et al 2011;Liu et al 2012).…”
Section: Introductionmentioning
confidence: 99%